1995
DOI: 10.1104/pp.108.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar H+-Translocating Pyrophosphatase Is Induced by Anoxia or Chilling in Seedlings of Rice

Abstract: Many plants are subjected to temporary anoxia or hypoxia as a result of flooding, waterlogging, or ice encasement. Among crop plants, rice (Oryza sativa L.) is the most tolerant of anoxic conditions (Mocquot et al., 1981), and corn (Zea mays L.) is also moderately tolerant (Johnson et al., 1989). In seedlings of these species, a number of metabolic changes have been observed in response to hypoxia, and evidence has been presented that at least some of these responses are adaptive, i.e. they increase the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 39 publications
(53 reference statements)
4
90
1
Order By: Relevance
“…A simultaneous up-regulation in the levels of H Ï© -PPase and PFP have been detected during anoxia in rice (Oryza sativa) seedlings (Mertens et al, 1990;Carystinos et al, 1995;Drew, 1997). Table I shows that the levels of PFP and H Ï© -PPase activities detected in different plants (Hajirezaei et al, 1994;Nielsen and Stitt, 2001) were sufficient in our assays to promote the formation of a H Ï© gradient.…”
Section: Table II Pp I Formation In Presence Of F16bp P I and F6pmentioning
confidence: 66%
“…A simultaneous up-regulation in the levels of H Ï© -PPase and PFP have been detected during anoxia in rice (Oryza sativa) seedlings (Mertens et al, 1990;Carystinos et al, 1995;Drew, 1997). Table I shows that the levels of PFP and H Ï© -PPase activities detected in different plants (Hajirezaei et al, 1994;Nielsen and Stitt, 2001) were sufficient in our assays to promote the formation of a H Ï© gradient.…”
Section: Table II Pp I Formation In Presence Of F16bp P I and F6pmentioning
confidence: 66%
“…Although DET3 appears to be a single-copy gene, we cannot exclude functional redundancy due to the presence of the H + -pyrophosphatase, a second proton pump specific to plants and phototrophic bacteria (Rea and Poole 1993). For instance, in det3 roots the H + -pyrophosphatase, which is highly active under anoxic conditions (Carystinos et al 1995), could be responsible for the lack of a strong root growth phenotype. Finally, we have shown that the hypocotyl elongation defect is conditional and most likely due to an increased V-ATPase assembly that is at least partially independent of the presence of DET3.…”
Section: The Det3 Mutant Does Not Show a General Defect In Cell Expanmentioning
confidence: 99%
“…PPi is also needed for the activity of the PPi-dependent vacuolar H 1 translocase (H 1 -PPase; Fig. 2; Carystinos et al, 1995). Activity of PEP carboxylase (PEPC) is repressed under anoxia (Fig.…”
Section: Anaerobic Responses In Ricementioning
confidence: 99%